Penggunaan Akun Bot Media Sosial untuk Mempengaruhi Opini Publik : Sebuah Tinjauan Hukum Di Indonesia - Devi Rahma Fatmala; Amanda Amelia; Fitri Agustina Trianingsih (Ajudikasi : Jurnal Ilmu Hukum, 2020)
Today’s political discourse can’t be disattached from the usage of social media. There are plenty of political actors using it to campaign their issues and attack their political rival in order to influence public opinion. One of the instruments used by the political actor in using the social media is bot accounts. Bot accounts are an automated online account where all or substantially all of the actions or posts of that account are not the result of a person. The usage of bot accounts are viewed as harmful for democracy by many experts on law and democracy. However, a lot of states have no regulation regarding the usage of bot accounts, including Indonesia. This article is intended to bring legal review on the usage of bot accounts to influence public opinion in Indonesia. Using deliberative democratic theory, this article views that the usage of bot accounts could prevent the objective achievement of democracy based on UUD 1945. The authors recommend the regulation of bot accounts through the revision of UU No. 19 Tahun 2019 about Informasi dan Transaksi Elektronik with bringing up various important argumentations regarding the law implementation. Keywords : Bot Accounts; Social Media; Public Opinion; Democracy; Legal Review.